Rural Extension: The Vital Linkage Between Research and Agricultural Production. Coffee Experiences - Sierra Sánchez, Néstor Fabián (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Rural extension plays an essential role in the connection between research and agricultural production. It is defined as the organizational process in which communities meet to acquire knowledge and technologies applicable to their farms. Its objectives include disseminating technical knowledge, promoting new technologies, and improving farmers' production and quality of life. The relationship between research and agricultural production is evident in the development and sustainability of coffee cultivation in Colombia. Coffee is the country's primary agricultural export. The National Coffee Research Center (Cenicafé, for its acronym in Spanish) has conducted research that has contributed to the development of resistant coffee varieties. Rural extension programs have facilitated the transfer of this and other technologies to coffee growers, resulting in improved productivity, sustainability, and quality of life. The adoption of new technologies by agricultural producers follows a process that includes stages such as knowledge, persuasion, decision, implementation, and confirmation. Rural extension employs individual, group, and mass methods to disseminate information, enabling farmers to adopt technologies that contribute to the resolution of problems that arise in production processes. Research in the coffee sector, led by Cenicafé, has been crucial. For example, the development of rust-resistant varieties has had a positive impact on profitability and environmental conservation. However, the application of research faces challenges such as limited resources, time, and resistance to change. Extension in Colombian coffee farming encounters comparable challenges but also offers prospects, such as certifying sustainable coffees and exploring tourism and agrotourism. Therefore, it is crucial to reinforce rural extension with the backing of diverse stakeholders and policies.